ECONOMIC FACTORS AS ONE OF INTERCULTURAL FEATURES NEGOTIATING IN INTERNATIONAL MANAGEMENT - BADALOV, Shahriyar (Annals of Spiru Haret University. Economic Series, 2018)
Cultural varieties between negotiators are constant in international business negotiation processes. In our modern world, there is a rapid development of international connections in all kind of spheres of human activity. The major aim of this study is to analyse and develop knowledge on the characteristics of intercultural negotiation that will give opportunities to the national representatives to be determined to their particular types of cultures, as well as to endow the characteristics of different countries in some business spheres. On a regular basis, in order to manage the expectations of the other party to the negotiations, it is important to discover the values of the associated partner at the supply stage and to try to manage all the information in the negotiation process, understanding the values and context of the other party involved in the negotiation process in the right place in order to make somewhat useful expectations from the other side, which would help to escape new conflicts in various business bargaining processes. In general, is notable from everyone that culture impacts the time, the style, and the course of the negotiation process. If prevented, cross-cultural connections may weaken an organization’s position in the market, protect it from fulfilling its purposes and eventually lead to reverse of negotiation. The research paper is focused in the scientific discussion part on the impact of intercultural negotiations on the international business environment, it can ensure inspiration and guidance for entrepreneurs, as well as helping them to understand the complexity of economic factors as one of the intercultural negotiating features which is of more interest for the students who are working on cultural diversity and its impact on business. This research thoroughly connects the characteristics of various national cultures with different areas of international business and tries to show the relationship and complexity of international negotiation issues in different contexts. The article should be useful resource for experts, students and researchers who are conducting more research in this sphere.